2012
DOI: 10.1097/icl.0b013e31825fed57
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Variations of Tear Osmolarity and Tear Meniscus Volume

Abstract: Objectives To determine the pattern of variations in tear osmolarity and tear meniscus volume in dry eye patients and in healthy control subjects over an 8-hour daytime period. Methods Ten normal subjects (5 males and 5 females with a mean age of 27 ± 7 yrs) and 10 dry eye patients (4 males and 6 females with a mean age of 36 ± 12 yrs) who had been diagnosed on the basis of having an ocular surface discomfort index (OSDI) >12 and a tear breakup time of < 10 seconds or Schirmer’s test score of < 5 mm were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 38 publications
(63 reference statements)
4
29
1
2
Order By: Relevance
“…This result agreed with that of Webber et al 61 who using fluorophotometry and reported that the morning tear turnover rate was higher than the afternoon rate in healthy subjects, which suggested a circadian rhythm in tear flow, and which also was suggested for aqueous tear evaporation, 62 tear meniscus height, 54 and tear film stability, 63 tests that might be related to the T-FCT results. Also, it has been found a daily variation of visual function, keratitis, conjunctival hyperemia and symptoms in DED subjects.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result agreed with that of Webber et al 61 who using fluorophotometry and reported that the morning tear turnover rate was higher than the afternoon rate in healthy subjects, which suggested a circadian rhythm in tear flow, and which also was suggested for aqueous tear evaporation, 62 tear meniscus height, 54 and tear film stability, 63 tests that might be related to the T-FCT results. Also, it has been found a daily variation of visual function, keratitis, conjunctival hyperemia and symptoms in DED subjects.…”
Section: Discussionsupporting
confidence: 94%
“…53,54 Li et al 54 recently reported diurnal variations in tear osmolarity and found that osmolarity was unaffected by the time of day in normal subjects.…”
Section: Discussionmentioning
confidence: 98%
“…These results are consistent with freezing point depression 9 and microosmometric 18 studies that found hypoosmotic tears upon awakening. Our TO is also consistent with the normal average TO of 301.8 6 10.5 mOsm/L reported by TearLab 13a and Li et al 19 who reported normal daytime TO of 298.0 6 14.2 mOsm/L also measured by TearLab Osmometer with a similar subject mean age of 27 6 7 years. Of interest, the results from our study support the hypothesis that normal eyes have a robust homeostatic system, which maintains a stable tear film in response to ordinary environmental stresses over waking hours.…”
Section: Discussionsupporting
confidence: 81%
“…Naked eye (i.e., no contact lens) TMV values obtained here are similar to those provided by García-Lázaro et al [45] (1.35 ± 1.18 L). However, the values of LTMV obtained by Li et al [46] are quite lower than ours. They determined TMV (both upper and lower) over 8-h period.…”
Section: Discussioncontrasting
confidence: 72%